Peran Guru PAI Dalam Membentuk Karakter Siswa pada Pembelajaran PAI di Sekolah Umum - Daffa Tsaqif Aufa; Ahmad Darlis; Fitrah Wahdania Ali; Wanda Ramadhani Br Samura; Yulia Ningsih (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The background of writing this article is the amount of delinquency among students. The purpose of this research is to look at the role of PAI teachers as educators in building student character. This study uses a literature study research method. The information and sources used to make this article come from relevant books and journals. This writing technique is a literature study of materials and data that have been collected, arranged logically and methodically arranged. The entire content of the article consists of theory and then conclusions are used to draw conclusions. Regarding his role as a PAI teacher in building student character, it includes: Empowerment, exemplary, intervention, integrated, filtering. The strategies carried out by PAI teachers to build student character include: 3S habituation (greetings, greetings, smiles), habituation of dhuha and asr prayers in congregation, habituation of reading short letters, reading prayers, habituation to discipline, habituation to be honest. Keywords: Role of PAI teacher, Student character